328 Validation of Eric - A New Parental Report Instrument for Detection of Cognitive Delay in At-Risk Infants. (October 2012) - Schafer, G; Genesoni, L; Jones, R; Doll, HA; Adams, E; Gray, R; Boden, G
Abstract : Background and Aims: At 2 years, cognitive delay is the most common form of developmental disability in the preterm population (Marlow, 2004). We have established the diagnostic properties of a new cognitive developmental screen (Early Report by Infant Caregivers, ERIC), between 10–24 months. Methods: Participants. 362 infants aged 10–24 months, with at least one of: weight < 1500g, < 34 completed weeks gestational age, 5-min Apgar < 7, HIE. Children with impairments preventing fair assessment by ERIC were excluded. Parents/caregivers completed ERIC at home before administration of the Cognitive Scale of the Bayley Scales of Infant Development III. Delay was defined as a prematurity-corrected Bayley score < 80 (Moore et al, 2011). Results: Nineteen infants were delayed, with age-corrected ERIC scores lower than those without delay (p<0.001). On ROC analysis, Area Under the Curve was 0.86, with 83% sensitivity (95% CI 66–99.9%), 79% specificity (75–83%), 19% Positive Predictive Value (PPV) (2–36%), and 98% Negative Predictive Value (NPV) (96–99.6%). The low PPV reflects low prevalence of delay (5.2%) in this sample. Conclusions: ERIC provides a useful diagnostic screening tool, able to rule out developmental delay in this population (NPV = 98%). Note: This abstract presents independent research funded by the National Institute for Health Research (NIHR) under its Research for Patient Benefit (RfPB) Programme (Grant Reference PB-PG-0807–14202). The views expressed are those of the authors and not necessarily those of the NHS, the NIHR or the Department of Health. Preliminary results were presented to the Neonatal Society, London, March 2012.